ANALYSIS IMPLEMENTATION OF THE SUPERVISION ROLE COMMISSION IX OF DPR RI IN THE HEALTH PROGRAM FOR THE 2014-2019 PERIOD: CASE STUDY IN THE PRIMARY CARE DOCTOR PROGRAM - Bahar, Ardiansyah; Achadi, Anhari (UI Scholars Hub, 2021)
Prolonged health problems have been recurring for a long time have raised questions about health program and its supervisory. The supervisory function carried out by Commission IX of the DPR RI on its partners from the government continues to be carried out in various ways. However, analysis has never been conducted to assess whether the various supervisory activities have been effective. This study uses a qualitative method based on phenomena, symptoms, facts, or social informants. Informants are determined directly based on the principles of appropriateness and adequacy. The data is then converted into transcript form, then analyzed, and a Logical Framework is created. This study shows that Commission IX's supervision of the Primary Care Doctor (Dokter Layanan Primer/DLP) Program is ineffective because the program is regulated in the Medical Education Law which is a product of Commission X DPR RI and involves The Ministry of Research and Education (Kemenristekdikti), which is not a working partner of Commission IX DPR RI. Supervision by Commission IX of DPR RI on work partners can positively influence partners' performance improvement. However, it is difficult to conclude that the increase in performance is entirely due to oversight from Commission IX of DPR RI. The supervisory function of Commission IX DPR RI for the DLP Program did not work effectively because the program was regulated in the Medical Education Law which was a product of Commission X DPR RI and involved Kemenristekdikti which was not a working partner of Commission IX DPR RI.